Thiamine pharmaconutrition in sepsis: current evidence on safety and efficacy - Gil Hardy; William Manzanares (Indonesian Nutrition Association, 2023)
Sepsis is a life-threatening condition characterized by multiorgan dysfunction due to an exaggerated host response to infection associated with a homeostatic failure. Sepsis is also characterized by low thiamine levels, which are associated with illness severity, hyperlactatemia, and poor clinical outcomes. However, caution is needed with interpretation of thiamine blood concentration in critically ill patients.